Presence of periodontal pathogen in preeclamptic women´s placenta: Literature review (Research, Society and Development, 2020)
Objective: To explore existing studies on the association between periodontal disease during pregnancy and pre-eclampsia, in view of the recent studies that periodontal pathogens can spread through fetal and placental tissues causing adverse effects on the health of the mother child. Method: Literature review carried out through scientific documents accessed in the MEDLINE, SCIELO and LILACS-BIREME databases, using the following descriptors: periodontal disease, microbiology, pre-eclampsia and pregnancy complications. The selection of studies was carried out through the collection and analysis of the most important references on the proposed theme. Literature review: The data collected show that the production and release of inflammatory mediators resulting from lesions in the periodontium also play an important role in the pathogenesis of preeclampsia, corroborating this association. Discussion: In addition, periodontal bacteria such as Porphyromonas gingivalis, Prevotella intermedia, Agregatibacter actinomycetemcomitans and Fusobacterium nucleatum ssp have been described as participants in the process of developing preeclampsia in pregnant women with periodontal disease. Conclusion: Knowledge about the adverse effects of pre-eclampsia in patients with periodontal disease may suggest contributions to an effective prenatal control with greater attention to dental care.